Serological Prevalence of Toxoplasma gondii Antibodies in Pregnancy in Palavecino Municipality. Lara State, Venezuela - María Triolo-Mieses; Luis Traviezo-Valles (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2006)
The sero-prevalence of anti-Toxoplasma gondii antibodies in 446 pregnant women with ages ranging from 15 to 43 years of age, living in the Cabudare and Agua Viva population, Lara State, Venezuela, was determined by using a commercial indirect hemagglutination test and considering titers1:16 as a positive reaction. Under this condition, 169 samples were positive (38%), 1:256 the most frequent titer (21%) and proportional increase of seroprevalence with age was observed.